Enhanced sequestration of methylene blue and crystal violet dye onto green synthesis of pectin modified hybrid (Pect/AILP-Kal) nanocomposite. (December 2021) - Ahmad, Rais; Ansari, Khalid
Graphical abstract: Highlights: A low-cost and green (Pect/AILP-Kal) nanocomposite was synthesized successfully. Kinetic data was best described by pseudo-second order model for the adsorbent. Isotherm data showed that the Langmuir model was best fitted with equilibrium data. The values of ΔH o and ΔG° confirms endothermic and spontaneous nature. Desorption of MB and CV dyes was performed successfully using 0.1 M HCl. Abstract: Herein, a low-cost and green adsorbent (Pect/AILP-Kal) was successfully synthesized from pectin modified with hybrid mixture of Azadirachta indica leaves and kaolin clay and further analyzed as an efficient adsorbent for sequestration of MB and CV dyes. Effect of the operational parameters, for instance concentration, temperature, dose, pH and contact time on adsorption characteristics were studied in detail. The optimum pH for sequestration of MB and CV was obtained at pH 7.5 with time of 180 min. Adsorption kinetics for MB and CV dyes was best followed with pseudo-second order. The equilibrium data showed that the Langmuir was best obeyed with an isotherm model. The endothermic and spontaneous nature was indicated by the positive ΔH° values and negative values of ΔG° calculated from the thermodynamic parameters. Breakthrough and exhaustive capacities were identified as being 16 and 76 (mg g −1 ) for MB while 20 and 72 (mg g −1 ) for CV dyes respectively. Desorption results showed that synthesized (Pect/AILP-Kal) nanocomposite can be reused upto fifth cycle successfully. In order to remove these hazardous dyes from aqueous solution, (Pect/AILP-Kal) nanocomposite can be utilized very effectively and economically.